"La mediación en los juicios de divorcio por mutuo consentimiento y su incidencia en los derechos fundamentales de las personas" - Ganchozo Mera, Ángela Narcita (2014)
The present artificial investigation is based in the reformation of the article 46 of the Law of Mediation and Arbitration, in which is recommended that the term of the presentation of the records of agreement of a mediation session is increased, with the purpose of improving the procedure of the mediation system. The artificial investigation this conformed to the following chapters: Chapter I, in which is developed the introduction, problematización, formulation of the problem, justification, objectives and hypothesis fundamental step of the investigation. Chapter II, in this I surrender it is given to know the theoretical, conceptual and legal foundation in the one that this based the investigation. Chapter III, in this part the methodology is detailed used to carry out the investigation, as the investigation types, methods, technical and instruments applied to reach the objectives of the investigation. Chapter IV in this section the results obtained based on the interviews and surveys carried out in good faith to the community are developed, mediator, and users of the mediation system Chapter V, in which the conclusions and recommendations obtained according to the investigation, is presented